Camphor-derived chiral auxiliaries in asymmetric synthesis - Molema, Warner Evert (Rhodes University, Faculty of Science, Department of Chemistry, 1998)
The investigation has been focussed largely on the chemistry and stereo-directing potential of camphor-derived compounds. The major regioisomer produced on partial hydrolysis of N-benzylcamphorimide was identified, by one- and two-dimensional NMR and X-ray crystallography, as (+)-(1S,3R)-(N-enzylcarbamoyl)-2,3,3-trimethylcyclopentanecarboxylic acid, the methyl ester of which was shown to undergo an unexpected intramolecular rearrangement during LAH reduction to afford (1S,3R)-Nbenzyl-3-hydroxymethyl-2,2,3-trimethylcyclopentane carboxamide. Several tartrate- and camphor-derived diols have been investigated as chiral auxiliaries in various asymmetric reactions of corresponding acetals of α,β-unsaturated aldehydes. MCPBA epoxidation of the tartrate-derived acetals afforded epoxy acetals in 4-12% diastereomeric excess. The camphor-derived acetals were obtained solely as the exosubstituted diastereomers, the stereochemistry being confirmed by two-dimensional NMR spectroscopy and X-ray crystallography. Simmons-Smith cyclopropanation of these camphor-derived acetals afforded cyclopropyl products with diastereoselectivities of 4% d.e. for the bornane-2,10-diol acetal and 46->99% d.e. for the bomane-2,3-diol acetals. In order to increase diastereofacial selectivity, a camphor-derived diol having a bulky substituent at C-10 was prepared, viz., phenyl 2,3-dihydroxybomane-10sulfonate, and α,β-unsaturated acetals of this diol were shown to undergo Simmons-Smith cyclopropanation with complete topological control (>99% d.e.), the diastereoselectivities being conveniently determined by ¹H and ¹³C NMR spectroscopy. Computer modelling, with the software package HYPERCHEM®, was used to explore the stereochemical aspects of the Simmons-Smith cyclopropanation, and hydrolysis of one of the cyclopropyl acetals has permitted the diastereoselective bias to be confirmed. (+)-Pinane-2,3-diol was also investigated as a chiral auxiliary in the Simmons-Smith reactions of α,β-unsaturated aldehydes, and moderate diastereoselectivities (20-30% d.e.) were observed. In a series of exploratory studies, the Diels-Alder reaction of the 2,3-dihydroxybomane-10-sulfonate acetal of trans-cinnamaldehyde with cyclopentadiene afforded a single cycloadduct, while OSO₄ dihydroxylation, MCPBA oxidation and alkylation of chiral acetals produced from both bomane-2,3-diol and phenyl 2,3-dihydroxybomane-10-sulfonate were less selective.
Keywords: Asymmetric synthesis; Chirality; Camphor